HSP-129 Population Change and the Housing Market in Alberta - Kevin McQuillan (The School of Public Policy Publications, 2025)
The collapse of oil prices in 2014 signaled trouble for the Alberta economy and quickly led to widespread layoffs in the oil and gas sector as well as in other industries reliant on activity in the energy sector. The economic downturn that followed influenced demographic trends as well. Interprovincial migration, typically a contributor to population growth in Alberta, turned negative with more people leaving the province than arriving. Of special concern was the growing exodus of young people. Alberta became less attractive to newcomers to Canada as well. And Alberta’s birth rate declined as well.